Magnetoelectric coupling of domains, domain walls and vortices in a multiferroic with independent magnetic and electric order - Marcela Giraldo (Nature Portfolio, 2021)
In h-RMnO3, the linear magnetoelectric effect is symmetry forbidden. Here, the authors show a pronounced magnetoelectric coupling driven by superexchange interaction giving rise to types of topological defects like magnetoelectric domain walls and vortex-like singularities.